Hipomelanose macular progressiva: estudo epidemiológico e resposta terapêutica à fototerapia Progressive macular hypomelanosis: an epidemiological study and therapeutic response to phototherapy - Ida Duarte; Bianca Ishimoto Della Nina; Maria Clara Gordiano; Roberta Buense; Rosana Lazzarini (Sociedade Brasileira de Dermatologia, 2010)
FUNDAMENTOS: A hipomelanose macular progressiva é uma dermatose comum em diferentes continentes. Sua causa é desconhecida e os tratamentos propostos são pouco eficazes. OBJETIVOS: Determinar aspectos epidemiológicos da hipomelanose macular progressiva em pacientes atendidos num setor de fototerapia, no período de 1997 a 2008, e avaliar a resposta terapêutica com PUVA ou UVBNB. MÉTODOS: Foram avaliados 84 pacientes com Hipomelanose Macular Progressiva. Após 16 sessões de fototerapia, a resposta terapêutica foi definida: I=inalterado, MD=melhora discreta(< 50% de repigmentação), MM=melhora moderada(50-79%), MI=melhora intensa(80-99%) e C=cura(100%). Após um tempo mínimo de três meses, pacientes com cura ou MI foram contatados por telefone para avaliar a manutenção do resultado terapêutico. RESULTADOS: Predominaram mulheres (79%) e a cor branca. A idade mínima de aparecimento da Hipomelanose Macular Progressiva foi de 13 anos e a máxima de 36 anos. Fototerapia com PUVA foi indicada em 27 pacientes e UVBNB em 57. Estatisticamente, não houve diferença significante entre o tratamento com PUVA e UVBNB (teste de Fisher P>0.05). A maioria (81%) dos pacientes obteve 50% ou mais de repigmentação e 65% tiveram cura ou MI. Entretanto, 72% apresentaram recorrência das lesões. CONCLUSÃO: A ausência de pacientes, com mais de 40 anos, sugere que a Hipomelanose Macular Progressiva seja uma doença autolimitada. Tanto PUVA como UVB NB são opções terapêuticas, porém não impedem a recidiva da doença. BACKGROUND: Progressive macular hypomelanosis is a common dermatosis in various continents. Its cause is unknown and proposed treatments have had little effect. OBJECTIVES: To determine epidemiological aspects of progressive macular hypomelanosis in patients referred to a phototherapy clinic between 1997 and 2008 and to evaluate therapeutic response to PUVA (psoralen + UVA) photochemotherapy or narrowband UVB phototherapy. METHODS: Eighty-four patients with progressive macular hypomelanosis were evaluated. After 16 phototherapy sessions, therapeutic response was classified as: unchanged, slightly improved (<50% of repigmentation), moderately improved (50-79% of repigmentation), much improved (80-99%) or cured (100%). After a minimum of three months, patients whose response was classified as cured or much improved were contacted by telephone to evaluate the persistence of the therapeutic response. RESULTS: Most of the patients were women (79%) and white (85%). Age at onset of progressive macular hypomelanosis ranged from 13 to 36 years. PUVA was prescribed for 27 patients and narrowband UVB phototherapy for 57. No significant difference was found between the outcomes obtained with PUVA and those obtained with narrowband UVB phototherapy (Fisher's exact test; p<0.05). The majority of patients (81%) had 50% or more repigmentation, with 65% being classified as cured or much improved. Nevertheless, there was a recurrence of the lesions in 72% of patients. CONCLUSIONS: The fact that no patients were over 40 years of age suggests that progressive macular hypomelanosis is a self-limiting disease. Both PUVA and narrowband UVB are effective therapeutic options; however, they do not prevent recurrence of the disease.